2019
DOI: 10.1038/s41422-019-0152-9
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus infection induces RNAi-mediated antiviral immunity in human neural progenitors and brain organoids

Abstract: The re-emergence of Zika virus (ZIKV) in the Western Hemisphere has resulted in global public health crisis since 2015. ZIKV preferentially infects and targets human neural progenitor cells (hNPCs) and causes fetal microcephaly upon maternal infection. hNPCs not only play critical roles during fetal brain development, but also persist in adult brain throughout life. Yet the mechanism of innate antiviral immunity in hNPCs remains largely unknown. Here, we show that ZIKV infection triggers the abundant productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
145
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 69 publications
5
145
2
1
Order By: Relevance
“…For example, novel anti-ZIKV activities of enoxacin, amodiaquine and niclosamide were discovered recently using human neural progenitor cells, human pluripotent stem cell-derived cortical neural progenitor cells, and human induced neural stem cells, respectively (Cairns et al, 2018;Xu et al, 2019;Zhou et al, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…For example, novel anti-ZIKV activities of enoxacin, amodiaquine and niclosamide were discovered recently using human neural progenitor cells, human pluripotent stem cell-derived cortical neural progenitor cells, and human induced neural stem cells, respectively (Cairns et al, 2018;Xu et al, 2019;Zhou et al, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…While this review was in production, a study reported that Zika virus (ZIKV) infection resulted in the production of canonical viRNAs in human neural progenitor cells (hNPCs), the major target cells of ZIKV, but not in neurons differentiated from hNPCs (Xu et al, ). This study supports the notion that RNAi can play an antiviral role in certain progenitor cells, including those involved in brain development.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…For mammals, vRI-dsRNAs and other viral nucleic acids usually induce innate antiviral immunity such as the type I interferon (IFN-I) system (1). Recently, accumulating evidence have provided strong support for the existence of antiviral RNAi in mammals (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%